Vertebral Artery Hypoplasia and Posterior Circulation Vulnerability: A Systematic Review of Epidemiological, Hemodynamic, and Clinical Evidence - Olja Mirkovic; Milos Stepovic; Jovana Milosavljevic; Maja Vulovic; Ivana Zivanovic-Macuzic; Dejan Aleksic; Milos N. Milosavljevic; Melanija Tepavcevic; Ivona Marinkovic; Simonida Delic; Kristijan Jovanovic; Verica Vukicevic; et al. (Neurology International, 2026)
Background/Objectives: Vertebral artery hypoplasia is a common congenital anatomical variant of the vertebral arteries, traditionally considered a benign finding. However, accumulating evidence suggests that VAH may influence vertebrobasilar hemodynamics and contribute to susceptibility to posterior circulation disorders. This systematic review aimed to synthesize current evidence regarding the epidemiology, hemodynamic significance, neurological manifestations, and cerebrovascular outcomes associated with VAH. Methods: This systematic review was conducted according to the PRISMA 2020 guidelines and registered in PROSPERO (CRD420261442242). A systematic search of PubMed/MEDLINE was performed from database inception to 8 June 2026, supplemented by manual reference screening and targeted searches. Studies evaluating VAH diagnosed using vascular imaging or anatomical assessment, including CTA, MRA, Doppler ultrasonography, and DSA, were eligible. Methodological quality was assessed using Joanna Briggs Institute critical appraisal tools, and the level of evidence was classified according to the Oxford Centre for Evidence-Based Medicine framework. Results: Forty-six studies were included in the qualitative synthesis. VAH prevalence varied substantially according to imaging modality, diagnostic criteria, and study population, ranging from approximately 3% to nearly 50%. Across clinical cohorts, VAH was frequently associated with posterior circulation ischemic stroke, transient ischemic attack, and vertebrobasilar insufficiency. Hemodynamic studies demonstrated reduced vertebral artery flow, increased vascular resistance, impaired cerebrovascular reactivity, and altered collateral flow redistribution. VAH was also associated with vestibular disorders, non-stroke neurological syndromes, vertebral artery dissection, and other cerebrovascular anatomical variations. Unlike previous reviews focusing primarily on prevalence or stroke associations, this review integrates epidemiological, anatomical, hemodynamic, computational, and neurological evidence within a unified clinically oriented framework and proposes an evidence-informed conceptual model of VAH as a context-dependent low-flow vascular susceptibility phenotype. Conclusions: Current evidence indicates that VAH represents a clinically relevant vascular susceptibility phenotype rather than merely an incidental anatomical variant. Its clinical significance appears to depend on the interaction between reduced vertebral artery flows, collateral capacity, vascular remodeling, and acquired cerebrovascular risk factors. Standardized diagnostic criteria and prospective multimodal studies are required to define its role in future cerebrovascular risk assessment.